Accuracy of the estimated prevalence of obesity from self reported height and weight in an adult Scottish population. Issue 2 (1st February 2000) - Bolton-Smith, Caroline; Woodward, Mark; Tunstall-Pedoe, Hugh; Morrison, Caroline
Abstract : STUDY OBJECTIVE: To determine whether self reported heights and weights from Scottish adults can provide an accurate assessment of obesity prevalence in the population. DESIGN: Standardised clinic measurements of weight and height were compared against self reported values on a postal questionnaire in the fourth Scottish MONICA cross sectional study. SETTING: A sex and five year age band stratified random population sample drawn from general practitioner registers in north Glasgow in 1995. Response rate 63% for men and 62% for women. PARTICIPANTS: A total of 865 men and 971 women aged between 25 and 64 years. RESULTS: Men and women under-reported their weight by a mean (SD) of 0.63 (3.45) kg and 0.95 (2.64) kg respectively, and their height by a mean (SD) of 1.3 (2.50) cm and 1.7 (2.37) cm respectively. Estimated body mass index, BMI (kg/m 2 ) varied from true (measured) BMI by +0.19 (1.40) for men and by +0.17 (1.34) for women. The only age/sex group in which BMI was under-estimated from self reports (mean 0.2) was the 55–64 year old women. Prediction equations that explained 90% (men) and 88% (women) of the difference between self reported and measured height included age and self reported weight. The equivalent prediction equations for weight explained 93% of the difference between self reported and measured weight for men and included smoking and diabetic status, while for women 96% of the variance was explained with no further variables being significant. Sensitivity and specificity for determining clinical obesity (BMI⩾30) were 83% and 96% respectively for men, and 89% and 97% for women. CONCLUSIONS: This Scottish population was unique in the under-reporting of height as well as weight, which resulted in BMI estimates with low error. These data suggest that self reported weights and heights would be satisfactory for the monitoring of obesity prevalence in Scotland.